Zmiana modelu nauczania studentów... - Jane Curry (Jesuit University Ignatianum in Krakow, 2017)
American higher education has begun a shift from professors delivering information to students to faculty as facilitators and assessors of student learning. The process of opening up for students to learn by doing and discovering has not only begun to change how education is done but has also created tensions. In this process, Jesuit-Catholic education has added extra dimensions.